Depolarization of the hydrogen evolution reaction on cadmium electrodes in alkaline media - Saidman, Silvia Beatriz (1988)
Depolarization of the hydrogen evolution reaction on high purity polycrystalline cadmium electrodes in alkaline media (12≦pH≦14 and 5≦T≦55°C) produced by cathodization in the range of potential comprised between the Cd/Cd(OH)2 electrode potential and the net HER potential under solution stirring conditions has been studied. The depolarization effect depends on the perturbing potential programme and it is little affected by the alkaline cation in solution. Results are discussed in terms of three concurrent reactions, namely the electrochemical formation of Cd(OH)2 and soluble Cd(OH)3−, the HER and the electrocrystallization of cadmium renewing the fresh active sites for the HER, SEM micrographs of activated cadmium electrodes reveal a heterogeneous surface topography of the new cadmium layers.